Abortion after diagnosis of fetal anomaly: Psychometric properties of a German version of the individual level abortion stigma scale. - Franz Hanschmidt; Michaela Nagl; Johanna Klingner; Holger Stepan; Anette Kersting (PLoS ONE)
Background Diagnosis of fetal anomaly is a significant life event and social stigma can negatively impact on the well-being of women opting for an abortion. This study investigated the psychometric properties of a measure of stigma among women who had had an abortion after diagnosis of fetal anomaly in a German setting. Methods The Individual Level Abortion Stigma (ILAS) scale was translated into German. Psychometric properties of the ILAS scale were examined among 130 women with a history of an abortion after diagnosis of fetal anomaly. Individual and situational factors associated with stigma in the context of an abortion after diagnosis of fetal anomaly were explored. Results Factor analysis suggested a four-dimensional structure of the German version of the Individual Level Abortion Stigma scale (Cronbach's α, .83-.91), corresponding to the subscales of the original scale. Test-retest reliability was acceptable for the worries about judgment subscale, the self-judgment subscale, and the community condemnation subscale, but less convincing for the isolation subscale. Associations between the subscales and measures of depression, self-esteem and secrecy were found in directions consistent with theory. Women who did not perceive their fetus to have a low survival chance and women whose fetus was at higher gestational age reported higher levels of stigma, whereas higher perceived partner support was associated with lower levels of stigma. Limitation Generalizability of study results was limited, as participants were recruited from one clinic in Germany and the study had a response rate of 46.5%. Conclusions The ILAS subscales are largely reliable and valid measures to assess stigma among women who have had an abortion after diagnosis of fetal anomaly. Suggestions for improving the assessment of stigma experienced in this population are outlined. The scales can be useful in research aiming at investigating psychological outcomes of abortion after diagnosis of fetal anomaly and improving care structures.